Evaluation of a New Cerium Oxide-Bismuth Oxide-Based Nanobiocomposite as a Biocatalyst for Biodiesel Production - Anam Shahzadi (MDPI AG, 2021)
Biodiesel is a promising renewable energy source that can be used together with other biofuels to help meet the growing energy needs of the rapidly increasing global population in an environmentally friendly way. In search for new and more efficient biodiesel production methods, this work reports on the synthesis and use of a novel biocatalyst that can function in a broader range of pH and temperature conditions, while producing high biodiesel yields from vegetable oils. Biodiesel was synthesized by transesterification of non-edible Eruca sativa oil using a lipase from Aspergillus niger that was immobilized on cerium oxide bismuth oxide nanoparticles. The synthesized nanoparticles were first grafted with polydopamine which facilitated the subsequent anchoring of the enzyme on the nanoparticle support. The enzyme activity, pH and temperature stability, and reusability of the immobilized lipase were superior to those of the free enzyme. Following response surface methodology optimization, the highest biodiesel yield of 90.6% was attained using 5 wt% biocatalyst, methanol to oil ratio of 6:1, reaction temperature of 40 °C, pH of 7, and reaction time of 60 h. The produced biodiesel was characterized by Fourier transform infrared spectroscopy and its fatty acid methyl ester composition was determined by gas chromatography-mass spectrometry. Erucic acid methyl ester was identified as the major component in biodiesel, with 47.7 wt% of the total fatty acid methyl esters content. The novel nanobiocatalyst (Bi2O3·CeO2@PDA@A.niger.Lipase) has the potential to produce high biodiesel yields from a variety of vegetable oils.